Factors influencing the FELDA settlers' satisfaction towards services rendered by FELDA Technoplant Sdn Bhd: a case study at FELDA Kemendur, Melaka / Muhammad Afiq Samsi - Samsi, Muhammad Afiq (Faculty of Plantation and Agrotechnology, 2015)
This study provides insight into the factors that influencing FELDA settlers' satisfaction towards services rendered by FELDA Technoplant Sdn Bhd. In order to obtain the information , FELDA settlers were chosen as the respondent for this study. 92 settlers from 120 settlers that received services from FELDA Technoplant Sdn Bhd were analyzed. The research project was conducted at FELDA Kemendor, Melaka. This research is important to inform the FELDA Technoplant Sdn Bhd about settler's level of satisfaction towards their services since the quality services affect the livelihood such as economy to survive as a smallholder fanner. Further more, the satisfaction of settlers is important as a benchmark of FELDA Technoplant Sdn Bhd that needs to achieve. The variable in this research that was tested towards factor influence satisfaction are commitment, timeline, efficiency and integrity.